Where is the beef? Vantage point from the livestock supply chain - Mohamed, Zainal Abidin (Universiti Putra Malaysia Press, 2012)
The livestock sector is an important and integral component of the agricultural sector in Malaysia. It provides gainful employment and animal proteins for the population. Livestock farming includes the production of poultry meat, eggs, pork, beef, mutton and milkas food items. In addition, some animal species also produce by-products, such as skin, bones and feathers. Over the last decade, Malaysia has experienced rapid economic and population growth, leading to an upsurge in demand-driven consumption of livestock products. The non-ruminant sub-sector responded to this increased demand by increasing domestic supply of poultry, eggs and pork but in the ruminant sector, however, the production system was severely strained. The beef sub-sector in particular wasunable to cope with the increasing domestic demand resulting in the need for increased importation of frozen, chilled and fresh beef, along with beef cattle for slaughtering to keep up with consumer demand. While current domestic production of beef is able to meet 28% of domestic demand if no drastic measures are taken to revive the beef sub-sector it will definitely decline and Malaysia will be forced to depend on other countries to satisfy its domestic beef demand. The price elasticity of beef demand is inelastic which implies that the consumers are not sensitive to changes in its price. This is due to the availability of substitute products. Similarly the income elasticity for beef demand is also inelastic which implies that consumers are not influenced by changes in their incomes. Further, the beef sub-sector is found to be inefficient in terms of production and it also does not have comparative advantage. Comparative advantage may however be achieved with large scale beef farming. Thus beef can be considered as normal good. In order to increase the sufficiency level to 40% by 2020, Malaysia will require 250,000 heads of breeding stock over the 2010-2020. For future long term sustainable growth of its beef sub-sector Malaysia cannot remain dependent solely on imported breeding animals and will thus have to work on developing its own cow-calf systems or breed lots.